Improving Physiological Factors and Plasmid Stability of DE3 Host System (Asian Journal of Pharmaceutics (AJP), 2022)
Objective: The purpose of the study delineates the growth and plasmid stability of DE3 host system.Methods: Different concentrations of drugs, chemicals, and various frequencies of radiations were subjected tothe host system to verify the colony forming units, along with plasmid concentration and stability. Results: Amongchemicals, acridine orange showed highest effect on growth of DH5a, while among the drugs, danthrone showedmaximum effect on the growth of the organism. Radio frequency of 2GHz and low-intensity microwave radiationwere recorded as highest inhibitory effects. However, there is no significant effect in growth that was observedin exposure to UV rays. Conclusion: The present work discussed that, the effect of drugs, chemicals, radiofrequency, and microwave radiation has a huge effect not only on growth of organism but also concentration andstability of plasmid.